Perlindungan Perempuan Dari Kejahatan Seksual Dalam Pandangan Hukum Pidana - Muhammad Vazriyansyah (GLOBAL SCIENTS PUBLISHER, 2025)
This study discusses the legal issue concerning the weak protection for women who are victims of sexual crimes in Indonesia, despite the existence of the Criminal Code (KUHP) and Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS). The purpose of this research is to examine the forms of criminal law protection for victims and to assess the effectiveness of the implementation of these regulations. The method used is normative legal research with a statutory and conceptual approach through literature study. The results show that although the UU TPKS has expanded protection and emphasized victim recovery, there remains a gap between legal norms and their practical implementation. Contributing factors include the lack of understanding among law enforcement officers, social stigma toward victims, and suboptimal assistance mechanisms. Strengthening gender-sensitive training, increasing legal awareness, and improving inter-agency cooperation are needed to ensure more effective protection for women victims of sexual crimes.